THE EFFECT OF SOCIAL MEDIA AND FOREIGN TOURISTS’ ATTITUDE TOWARDS PURCHASING DECISION MAKING OF SPA TOURISM PRODUCTS IN UBUD TOURISM AREA, GIANYAR DISTRICT - Suci Arthini, Ni Nyoman (Universitas Pendidikan Ganesha, 2018)
This study aims to determine the effect of social media and the attitude of foreign tourists on making purchasing decisions on Spa tourism products in Ubud Tourism Area, Gianyar Regency. Determination of the sample was done by Purposive Sampling. Sampling is done accidentally. The sample in this study was 105 foreign tourists who had bought or used Spa products in Ubud Tourism Area, Gianyar Regency. The methods of data collection in this study were observation and questionnaire. In this study the data analysis techniques used were descriptive analysis, simple regression analysis, and multiple linear regression analysis. Based on the research that has been done, it was found that: 1) social media (X1) had a positive and significant effect on purchasing decisions (y) Spa tourism products in the tourism area of Ubud by 4,295, 2) attitude (X2) had a positive and significant effect on purchasing decisions (y) Spa tourism products in the tourism area of Ubud at 6.680, and 3) social media (X1) Attitudes (X2) have a positive and significant effect on purchasing decisions (y) Spa tourism products in the Ubud tourism area of 98.992. From these findings it can be concluded that there are influences of social media and the attitude of foreign tourists towards making purchasing decisions on Spa tourism products in Ubud Tourism Area, Gianyar Regency.